Linking local and heterogeneous deformation behavior to global deformation of materials by in-situ experimental techniques. (August 2019) - Tsuji, Nobuhiro; Park, Myeong-heom; Gao, Si; Bai, Yu; Chong, Yan
Abstract: Plastic deformation of metallic materials is essentially heterogeneous and localized. In the case of dislocation slip, for example, slip of dislocations occurs on particular crystallographic planes and in particular directions, and dislocations are multiplied from dislocation sources located on limited slip planes. Heterogeneous deformation is also induced by the constraint of adjacent grains in polycrystalline materials and appears in different length scales in the form of different slip patterns within each grain, deformation bands, and so on. To achieve higher strengths, the microstructures of structural metallic materials have become more and more complicated and are often composed of different phases (or domains) having different strength levels. In such complicated microstructures, deformation becomes even more heterogeneous. Therefore, it is important, especially in high strength metals, to link local and heterogeneous deformation aspects to the global deformation behavior, in order to fundamentally understand the nature of deformation and then to design advanced materials for performing desired mechanical properties. Conventional material testing, such as tensile tests can determine the global deformation behavior of materials, but the obtained stress-strain curves show only the average material response, in which local information is hidden. Local and heterogeneous characteristics of deformation have been observed by various kinds of microscopy, but it is typically difficult to correlate such local and heterogeneous features with the global and average materials response, especially during deformation. Recently, significant progress has been made in various kinds of in-situ experimental techniques, and a breakthrough in deepening the fundamental understanding of deformation of materials is expected. Such techniques include in-situ neutron/synchrotron diffraction during deformation, in-situ deformation observations in scanning and transmission electron microscopy, nano-indentation, and digital image correlation (DIC) during deformation. In the current paper, some recent results obtained in the author's group linking local and heterogeneous characteristics to the global deformation response for several metallic materials are introduced, illustrating the use of state-of-the-art techniques.